Maternal Pulse Pressure and the Risk of Postepidural Complications: A Randomized Controlled Trial. Issue 2 (June 2018) - Lappen, J.R.; Myers, S.A.; Bolen, N.; Mercer, B.M.; Chien, E.K.S.
Abstract : ( Obstet Gynecol . 2017;130(6):1366–1376) Neuraxial analgesia results in decreased maternal systemic vascular resistance and increased venous capacitance, which in turn can affect maternal blood pressure (BP) and uteroplacental blood flow. Such hemodynamic changes occur in the setting of constant maternal intravenous (IV) fluid preload. However, evidence supporting IV fluid preloading is conflicting. In the present trial, the authors evaluated whether a larger volume of IV fluid at the time of intrapartum epidural placement for women with a narrow pulse pressure decreased the frequency of postprocedure fetal heart rate (FHR) abnormalities. In addition, the authors assessed whether providing a larger volume of IV co-load to such women would decrease the frequency of maternal hypotension and resuscitative obstetric interventions.